Uniform Statistical Convergence on Time Scales - Yavuz Altin; Hikmet Koyunbakan; Emrah Yilmaz (Journal of Applied Mathematics)
We will introduce the concept of m- and (λ,m)-uniform density of a set and m- and (λ,m)-uniform statistical convergence on an arbitrary time scale. However, we will define m-uniform Cauchy function on a time scale. Furthermore, some relations about these new notions are also obtained.